Respostas
respondido por:
1
3x +2y= 60
x + y =20 multiplique por (-2)
logo tem se
3x +2y =60
-2x-2y= -40
corta 2y com -2y fica
3x - 2x = 60-40
x =20
substituindo
x+ y= 20
20 + y = 20
y = 20 -20
y = 0
logo (x;y) e igual ( 20 ; 0 )
x + y =20 multiplique por (-2)
logo tem se
3x +2y =60
-2x-2y= -40
corta 2y com -2y fica
3x - 2x = 60-40
x =20
substituindo
x+ y= 20
20 + y = 20
y = 20 -20
y = 0
logo (x;y) e igual ( 20 ; 0 )
renatareh2013reh:
Mano vlw d vdd
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás